Відновлення м'язового корсету обличчя при естетичній реабілітації = Restoration muscular face of rehabilitation aesthetic - I. Yu. Badyin; A. I. Gozhenko; O. L. Holodkova (Kazimierz Wielki University, 2015)
Badyin I. Yu., Gozhenko A. I., Holodkova O. L. Відновлення м'язового корсету обличчя при естетичній реабілітації = Restoration muscular face of rehabilitation aesthetic. Journal of Education, Health and Sport. 2015;5(4):264-272. ISSN 2391-8306. DOI: 10.5281/zenodo.16937 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A264-272   http://dx.doi.org/10.5281/zenodo.16937 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.03.2015. Accepted: 10.04.2015.   відновлення м'язового корсету обличчя ПРИ ЕСТЕТИЧНІЙ РЕАБІЛІТАЦІЇ RESTORATION muscular FACE OF REHABILITATION aesthetic   І. Ю. Бадьїн, А. І. Гоженко, О. Л. Холодкова I. Yu. Badyin, A. I. Gozhenko, O. L. Holodkova   ДП Український НДІ медицини транспорту МЗ України, м. Одеса Ukrainian Research Institute for Medicine of Transport, Odessa, Ukraine   Abstract Age-related changes of the skin of a face are part of the biological process of aging. The author writes about the improvement of the functional state of the facial muscular system the restoration ways with PRP-therapy. The mesotherapeutic and intra-muscular injection of the patient's blood plasma, enriched by platelets in the facial muscles and/or subcutaneously is the essence of the therapy. The advantages and the results of these therapeutical methods use are discussed in the article presented.. Keywords: PRP-therapy, stem cell, platelet, aesthetic medicine.   Резюме. Возрастные изменения кожи лица являются частью общего биологического процесса старения. В работе описан усовершенствованный способ восстановления функционального состояния мышечного корсета лица путем проведения PRP-терапии. Суть терапии состоит в мезотерапевтическом и внутримышечном введении препарата - плазмы крови пациента, обогащенной тромбоцитами в мимические мышцы и/или подкожно. В статье приводятся преимущества и результаты описанных методов терапии. Ключевые слова: PRP-терапия, стволовые клетки, тромбоциты, эстетическая медицина.